(untitled) (Raparin Journal of Humanities (RJH), 2020)
This research deals with a topic related to the size and type of gratifications achieved by the traditional and new media for the youth segment in the Kurdistan Region, due to the importance of the role that these means play and their influential and directive capabilities on the one hand, and the sensitivity of the structural reality of youth space, Especially for those who belongs to this senstive age group, so to speak. From here, the research aims to ensure the achievement of the physiological, security, social, psychological, and cognitive gratifications of the young recipient in the Kurdistan region by viewing the means of mass communication and social communication and their levels, as well as reaching the levels of what they accomplished in this field, separately, i.e., the mass and social means of the gratification, for the recipient In the Kurdistan region and reading its implications to answer what they indicate. This research is considered descriptive research that is appropriate to understand the details of its basic variables and the interrelationships that provide us with what is happening in its mutual influence space, by using survey and comparative survey methods in the practical aspect of it, relying on a sample of young people belonging to the age group within (15 -24) years old, of (172) respondents.